Analisis Ruas Jalan Nasional Klari Kabupaten Karawang Menggunakan Metode MKJI 1997 - Abdul Rokhman; Desi Putri; Sriyono D. Siswoyo (Sekolah Tinggi Teknik - PLN, 2022)
Road is one of the land transportation infrastructure that a very important role in maintaining the continuity of the distribution of goods and other services. A roads are also useful for human migration from one place to another. Road conditions that will affect performance are if the road is overloaded with traffic. In Karawang Regency, especially the Klari National Highway which is the main road in Klari sub-district, and is the entrance to the Karawang Timur toll road as the entry and exit gate for large vehicles, especially factory vehicles, private cars and other public transportation. In this study, we want to know the performance of the road on the Klari highway. The method used to determine the performance of the Klari highway is to use the Indonesian Road Capacity Manual (MKJI 1997). The survey was conducted during peak hours on Mondays. After doing the analysis and obtained the capacity of the Klari highway to the Cikampek direction of 3172 smp/hour with a degree of saturation of 0.44 and the level of service can be interpreted as being at level B and the capacity of the Klari highway to the direction of Karawang of 2937 smp/hour with a degree of saturation of 0, 49 and the level of service can be interpreted as being at level C.